Teaching writing in Turkish and German native language school books [Türkçe ve Almanca ana dili ders kitaplarinda yazma eǧitimi] - (:unkn) unknown (My University, 2011)
In order to be able to reach the optimum quality in education, it is absolutely necessary to provide an extensive, level-based language teaching method which will enrich the student by giving him both mental and emotional depth. The teaching of a native language is realized via the study of grammar and language skills. Writing is the last skill to be acquired but the most important language skill among the others which are listening, speaking and reading. Writing not only exposes the person's individual development but also his status in society. Considering this very reason, writing needs to be improved, and this activity should not only be confined to schools, but it has to find support in every area of society. Also, for the sake of individual development, writing needs to be further supported with activities such as creative writing. Reaching the level of free and creative writing can only be possible by putting emphasis on systematic and regular studies aimed at achieving this target. This PhD thesis published under the title of Teaching Writing in Turkish and German Native Language School Books of the 4th Grade in Primary Education (2007), aims to demonstrate via a comparative study of Turkish and German language books, how the writing skill, which essentially starts at elementary school, is handled in elementary school textbooks. This article aims to provide information about the results and comparative findings of the above mentioned thesis.
Keywords: 4th grade; German; Native language school books; Teaching writing; Turkish